Synergistic Solvent Extraction of Lanthanides (III) with Mixtures of Tetraphenylmethylenediphosphine Dioxide and Picrolonic Acid from HCl Solutions. Issue 2 (23rd February 2017) - Turanov, A. N.; Karandashev, V. K.
ABSTRACT: The solvent extraction of lanthanides(III) from hydrochloric acid solutions into the organic phase containing neutral bidentate extractant tetraphenylmethylenediphosphine dioxide (L) and picrolonic acid (HP) has been studied. A considerable synergistic effect was observed in the presence of HP in the organic phase containing neutral bidentate organophosphorus ligand. The extraction equilibrium was investigated and the equilibrium constants were calculated. It was found that the lanthanide(III) ions are extracted from weak acidic solutions as LnP3 L and LnP3 L2 complexes. The mixture L–HP offers higher extraction efficiency toward Ln(III) than mixtures of L with 1-phenyl-3-methyl-4-benzoyl-pyrazolone-5 or picric acid.